Sorghum headbugs and grain molds in West and Central Africa; I: host plant resistance and bugmold interactions on sorghum grains - Ratnadass, A.; Marley, P.S.; Hamada, M.A.; Ajayi, O.; Cissé, B.; Assamoi, F.; Beyo, J.; Cisse, O.; Dakouo, D.; Dossou-Yovo, S.; Le Diambo, B.; Vopeyande, V.; et al. (Elsevier, 2003)
A regional sorghum head-bug and grain mold resistance trial was conducted in 1996 and 1997 at 15 and 13 research stations located in 10 West and Central African countries, respectively. Two cultivars namely IS 14384 and CGM 39/17-2-2 exhibited consistently high levels of resistance both to head-bugs and grain molds over years and localities. Eurystylus oldi was the dominant head-bug species at all localities except in Benin, Chad and Guinea. Sorghum grain mycoflora varied little between sites with genera Phoma and Fusarium dominating, followed by Curvularia. Efficiency of the insecticidal treatment on head-bug incidence partially confirmed the critical role played by head-bugs in aggravating mold infection.